MicroRNAs: new players in IBD. Issue 3 (4th December 2014) - Kalla, R; Ventham, N T; Kennedy, N A; Quintana, J F; Nimmo, E R; Buck, A H; Satsangi, J
Abstract : MicroRNAs (miRNAs) are small non-coding RNAs, 18–23 nucleotides long, which act as post-transcriptional regulators of gene expression. miRNAs are strongly implicated in the pathogenesis of many common diseases, including IBDs. This review aims to outline the history, biogenesis and regulation of miRNAs. The role of miRNAs in the development and regulation of the innate and adaptive immune system is discussed, with a particular focus on mechanisms pertinent to IBD and the potential translational applications.